Wittgensteinian Method of Language-games and the Bystander Effect - Mendoza, Lumberto G. (Philippine Social Sciences Review, 2014)
The paper is a conceptual inquiry on the later Wittgenstein’s approach to ethics through an account of how the method of language-games applies to research on the bystander effect. Using the Kitty Genovese murder and the Wang Yue hit-and-run as sample cases, I cite findings on how the bystander effect involves confusion on action due to the ambiguity of the situation. I argue that the presence of this ambiguity is consistent with Wittgenstein’s view on the indeterminacy of language and that the method of language-games offers a solution via an approach of engaged reflection rather than abstract deliberation. The method of language-games deters the bystander effect by establishing a sensitivity that puts us in a better position to clarify and take the perspective of others. Emphasis on acquiring this sensitivity is significantly similar to how closeness and social learning facilitate social courage. I conclude by explaining how the method of language-games leads to a critical conception of agency that is fundamentally connected to a sense of the other and how closeness and social learning serve as concrete illustrations of how Wittgenstein’s method of language-games becomes applicable in practical ethics.
Keywords: Wittgensteinian ethics, method of language-games, bystander effect, social inhibition, plurality of ignorance, diffusion of responsibility, social courage